Perceptions and practices of mosquito-borne diseases in Alabama - is concern where it should be? - Wayde Morse; Katie Izenour; Benjamin McKenzie; Sarah Lessard; Sarah Zohdy (BMC, 2019)
Abstract Background The Gulf Coast of the United States is home to mosquito vectors that may spread disease causing pathogens, and environmental conditions that are ideal for the sustained transmission of mosquito-borne pathogens. Understanding public perceptions of mosquito-borne diseases and mosquito prevention strategies is critical for the development of effective vector control strategies and public health interventions. Here, we present a survey conducted in Mobile, Alabama along the Gulf Coast to better understand public perceptions of mosquito-borne diseases, mosquito control activities, and potential risk factors. Methods Using Knowledge, Attitude, and Practice (KAPs) assessments, we surveyed populations living in 12 zip codes in Mobile, Alabama using a 7-point Likert scale and frequency assessments. Survey participants were asked about vector control efforts, knowledge of mosquito-borne diseases, and understanding of mosquito ecology and breeding habitats. Results One hundred twenty-six surveys were completed in Mobile, Alabama, revealing that 73% of participants reported being bitten by a mosquito in the last 30 days and mosquitoes were frequently seen in their homes. Ninety-four percent of respondents had heard of Zika Virus at the time of the survey, and respondents reported being least familiar with dengue virus and chikungunya virus. Conclusions Chikungunya virus, dengue virus, malaria, West Nile virus, and Zika virus have been documented in the Gulf Coast of the United States. The mosquitoes which vector all of these diseases are presently in the Gulf Coast meaning all five diseases pose a potential risk to human health. The results of this survey emphasize knowledge gaps that public health officials can address to empower the population to reduce their risk of these mosquito-borne diseases. Each species of mosquito has specific preferences for breeding and feeding and there is no one size fits all prevention approach, educating people on the need for a variety of approaches in order to address all species will further empower them to control mosquitoes where they live and further reduce their risk of disease.